Perceived parental support and parental attitudes towards mental health help-seeking in relation to help-seeking behaviours and attitudes of Black and Black Mixed ethnicity young people in the UK - Kwakyewaa-Gyamfi, Olivia (2019)
Research evidence from various populations has shown parental support and parental stigma towards mental health and help-seeking to influence individual’s attitudes towards and actions of help seeking. This study explores perceived parental support and parental attitudes towards mental health help-seeking in relation to help-seeking behaviours and attitudes in Black and Black Mixed ethnicity young people in the UK. This was an online study, using a correlational-predictive design. Participants were required to fill out six questionnaires that measured levels of perceived parental support, parental attitudes towards mental health help-seeking, their own attitudes towards mental health help-seeking, likelihood of general help-seeking and actions of help-seeking. Results showed a significant relationship between parental support and likelihood of general help-seeking, as well as a significant relationship between parental attitudes towards mental health help-seeking and all three of the outcome variables. These findings both support and contradict previous research in this field and offer an alternative perspective on the role of stigma/negative attitudes towards mental help-seeking in the likelihood and actions of help-seeking behaviour. Interpretation of the results, limitations of the study and implications of the findings in practice and future research are considered in the discussion.